Effects of novel brain‐penetrating oxime acetylcholinesterase reactivators on sarin surrogate‐induced changes in rat brain gene expression. Issue 6 (8th March 2021) - Dail, Mary E.; Brino, Meghan L. M.; Chambers, Janice E.
Abstract: Past assassinations and terrorist attacks demonstrate the need for a more effective antidote against nerve agents and other organophosphates (OP) that cause brain damage through inhibition of acetylcholinesterase (AChE). Our lab has invented a platform of phenoxyalkyl pyridinium oximes (US patent 9, 277, 937) that demonstrate the ability to cross the blood–brain barrier in in vivo rat tests with a sarin surrogate nitrophenyl isopropyl methylphosphonate (NIMP) and provide evidence of brain penetration by reducing cessation time of seizure‐like behaviors, accumulation of glial fibrillary acidic protein (GFAP), and hippocampal neuropathology, as opposed to the currently approved oxime, 2‐pyridine aldoxime methyl chloride (2‐PAM). Using two of the novel oximes (Oximes 1 and 20), this project examined whether gene expression changes might help explain this protection. Expression changes in the piriform cortex were examined using polymerase chain reaction arrays for inflammatory cytokines and receptors. The hippocampus was examined via quantitative polymerase chain reaction for the expression of immediate‐early genes involved in brain repair ( Bdnf ), increasing neurotoxicity ( Fos ), and apoptosis control ( Jdp2, Bcl2l1, Bcl2l11 ). In the piriform cortex, NIMP significantly stimulated expression for the macrophage inflammatory proteins CCL4, IL‐1A, and IL‐1B. Oxime 20 by itself elicited the most changes. When it was given therapeutically post‐NIMP, the largest change occurred: a 310‐fold repression of the inflammatory cytokine, CCL12. In the hippocampus, NIMP increased the expression of the neurotoxicity marker Fos and decreased the expression of neuroprotective Bdnf and antiapoptotic Bcl2l1 . Compared with 2‐PAM, Oxime 20 stimulated Bcl2l1 expression more and returned expression closer to the vehicle control values.